Non-persistence and non-adherence to long-acting COPD medication therapy: A retrospective cohort study based on a large German claims dataset. (January 2017) - Mueller, Sabrina; Wilke, Thomas; Bechtel, Benno; Punekar, Yogesh Suresh; Mitzner, Karen; Virchow, J. Christian
Abstract: Objectives: The main objectives of this study, based on a large cohort of German COPD patients, were to assess the level of non-persistence (NP) and non-adherence (NA) with long-acting COPD inhaler treatment and to describe factors that may be associated with NP and NA. Methods: This was a retrospective cohort analysis based on claims data provided by a German statutory health insurance fund (years 2010–2012). NP was analyzed for treatment-naïve patients only; it was defined as a gap of >90 days in medication availability. With regard to NA, first the overall yearly medication possession ratio (MPR) was analyzed, NA was defined as MPR<80%. Secondly, adherence was explored only for the period in which a patient continued therapy with a long-acting COPD agent (no gap>90 days). Results: 45, 937 COPD patients who received at least one prescription of any long-acting COPD agent were identified (mean age 71.4 years; 45.2% female). Among these, 22, 276 (42.4%) were classified as newly treated. The percentage of NP patients after 12 months was 65.3% on an overall patient level. Agent-specific NP rates were: 58.5% for LABA, 47.9% for LAMA, 78.0% for ICS, and 69.4% for single-device LABA/ICS combination treatment. The overall 12-month MPR across all agent classes on a patient level was 57.9% (70.0% of patients classified as non-adherent). During periods of general treatment continuation, the mean MPR/NA rates were 85.0%/30.1% (patient level across all agents), 89.3%/28.2% (LABA), 92.1%/16.2% (LAMA), 84.2%/43.8% (ICS) and 84.1%/42.8% (LABA/ICS combination). In the Cox regression analyses, several factors like female gender, higher CCI or lower number of specialist' visits were associated with earlier discontinuation of therapy. In comparison to LABA therapy, LAMA therapy was less likely to be associated with early NP, whereas patients who initiated ICS therapy or a single-device LABA/ICS combination therapy faced a higher NP risk. Conclusions: In German COPD patients, persistence and adherence with respect to long-acting bronchodilator therapy is poor. Approximately two thirds of patients fail to continue treatment after 12 months. In addition, about one third implement their treatment poorly during periods of general therapy continuation. Highlights: In German COPD patients, persistence and adherence in long term therapy is poor. Approximately two thirds of patients fail to continue treatment after 12 months. About one third implement their treatment poorly during periods of general therapy continuation.